Development of Tie Dye Technique and Its Impact On Students Learning Outcome and Fine Motor Development - Putri, Riska Yuliastanti; Ary, Deasylina Da (Universitas Negeri Semarang, 2019)
This study aims to develop a color barrier technique in the class III charge of Cultural Arts and Skills at SDN Purwoyoso 06 Ngaliyan, Semarang. This research is a Research and Development (RnD) research with steps namely: potential and problems, data collection, product design, design validation, design revision, product testing, product revision, usage testing, product revision, and final product. The population of this study was 42 third grade students of SDN Purwoyoso 06 Ngaliyan Semarang. Data analysis techniques use product data analysis, learning outcomes, and student activities. The results of the study showed: (1) the development of color barrier techniques, namely the media and tools used and the motives produced. Based on expert validation shows the color barrier technique in the test of learning techniques experts and material get a percentage of 96.4% and 97.5% with very feasible criteria; (2) the use of color barrier techniques influences the effectiveness of SBK learning as evidenced by student learning outcomes with an average student score of 78.33%; (3) student activities obtain an average percentage of 94.83% with very high criteria. The conclusions of the study showed that the results of the development of the color barrier technique based on the validation of the learning techniques experts and the material fulfilled the criteria were feasible, could improve the effectiveness of student learning and activity.